Determining the poolability of individual series in panel datasets - George Kapetanios (Queen Mary University of London, Department of Economics, 2003)
Panel datasets have been increasingly used in economics to analyse complex economic phenomena. One of the attractions of panel datasets is the ability to use an extended dataset to obtain information about parameters of interest which are assumed to have common values across panel units. However, the assumption of poolability has not been studied extensively beyond tests that determine whether a given dataset is poolable. We propose a method that enables the distinction of a set of series into a set of poolable series for which the hypothesis of a common parameter subvector cannot be reject and a set of series for which the poolability hypothesis fails. We discuss its theoretical properties and investigate its small sample performance for a particular simple model in a Monte Carlo study.
Keywords: C12; C15; C23; 330; Panel datasets; Poolability; Sequential testing; Statistischer Test; Panel; Monte-Carlo-Methode; Theorie; Varianzanalyse